Manfaat Canva untuk Melatih Kreativitas Pembuatan Mind Map Mata Kuliah Alat-Alat Ukur dan Instrumentasi - Handayani Parinduri, Sri (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
This study aims to explain the benefits of Canva, namely to train creativity in making mind maps for physics students. Canva is an application that allows users to create designs online. To access Canva, users can use cellphones, computers, laptops or tablets. The method used in this study is a qualitative method. Data collection techniques are carried out by tri-anggulation (combined) in the form of literature reviews by collecting data, especially verbal data through books, articles, notes, and various other scientific literature. The research population is all students of the physics tadris study program. The research sample is a fourth semester student of the physics tadris study program in the course of measuring instruments and physics instrumentation UIN Syahada Padangsidimpuan. The instrument used to determine the benefits of canva is a test of mind map making practices. The results showed that Canva can train students' creativity in making mind maps